AN ECONOMIC ANALYSIS OF THE DETERMINANTS OF DOMESTIC DEMAND FOR TEA IMPORTS IN IRAQ USING THE AUTOREGRESSIVE DISTRIBUTED LAG TECHNIQUE (ARDL) FOR THE PERIOD (1990-2020) - Kadhim, Zuhal R. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to estimate the domestic demand function on tea imports in Iraq using the Autoregressive Distributed Lag model (ARDL) for co-integration during the period 1990-2020.The data are verified for stationary by using unit root tests basis on Augmented Dickey - Fuller Test. The existence of a long-run equilibrium relationship among tea import quantity, current prices of tea and coffee buying, gross national income, and number of buyers is proved using bounds test method to co-integration. Results of estimating short and long-run models of the demand of tea imports by using the unrestricted error correction approach showed that the error correction parameter is adjusted annually by 140%. Results of estimating price elasticity of demand in the short run showed that the absolute coefficient of price elasticity of demand is less than one and more than zero, which means that tea is a necessary commodity for the Iraqi shopper. Additionally the cross elasticity coefficient had a positive sign in the short and long run, which means that coffee, is an alternative good for tea from the viewpoint of the Iraqi consumer. With regarding to the coefficient value of the income elasticity of demand, it was positive and less than one in the short and long run, which means that tea, is a necessary normal commodity for Iraqi buyers. The study recommended that it is necessary to diversify the sources of national income in the local economy by utilizing all available resources in order to reduce dependence on oil revenues, which were a major source of financing imports in the country.